At the genesis of Creole societies: ecological variation - (:unkn) unknown (My University, 2012)
Each group present during the genesis of Creole societies faced ecological variation and experienced radical changes in comparison to their societies of origin. Such was the case for the populations who had left their country to settle down in the plantation societies of the Americas. These peoples transformed their new environment and they were transformed by it. It was also the case for the native populations whose ecosystems were disrupted by the newcomers. The climatic change (from a European point of view) was a determining factor of the ecological variation. These tropical areas were modified by the import of non-European plants chiefly grown by the slaves deported from Africa. The ecology of the slave plantation has deeply structured the Creole societies, even though there was at the same time a peasantry of European origin that could not have access to large properties, or a peasantry of African origin who could free themselves from the influence of the large properties. Having introduced the general framework of this ecological variation (Plantation America), we will focus on the particular case of Martinique.
Keywords: African Research